Parastomal Hernia Repair with Intraperitoneal Mesh. (24th October 2017) - Näsvall, Pia; Rutegård, Jörgen; Dahlberg, Michael; Gunnarsson, Ulf; Strigård, Karin
Abstract : Purpose . Parastomal hernia is a common complication following a stoma and may cause leakage or incarceration. No optimal treatment has been established, and existing methods using mesh repair are associated with high recurrence rates and a considerable risk for short- and long-term complications including death. A double-layer intraperitoneal on-lay mesh (IPOM), the Parastomal Hernia Patch (BARD™), consisting of ePTFE and polypropylene, has been developed and tailored to avoid recurrence. To evaluate the safety of and recurrence rate using this mesh, a nonrandomised prospective multicentre study was performed. Method . Fifty patients requiring surgery for parastomal hernia were enrolled. Clinical examination and CT scan prior to surgery were performed. All patients were operated on using the Parastomal Hernia Patch (BARD). Postoperative follow-up at one month and one year was scheduled to detect complications and hernia recurrence. Results . The postoperative complication rate at one month was 15/50 (30%). The parastomal hernia recurrence rate at one year was 11/50 (22%). The reoperation rate at one month was 7/50 (14%), and further 5/50 (10%) patients were reoperated on during the following eleven months.